Rancang Bangun Programmable Logic Controller ( P L C ) Menggunakan Mikrokontroler Pic16f877 Sebagai Media Pembelajaran - Subiyanta, Erfan; Ibnu Analis, Faizul Wafa (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2025)
Programable logic control (PLC) is a versatile microprocessor control designed to meet practical demands in industry such as in the automatic field. In the automatic field serves as a substitute for an electro mechanical system that is to replace a series of series of relays found in conventional process control systems. Therefore, in this thesis, a research on Design (PLC) Programable Logic Controller Based on PIC16F877 Microcontroller as Learning Media has been conducted.This Micro PLC consists of a minimum system PIC16F877 microcontroller circuit. Micro PLC testing only takes a few sample cases such as I / O (input output) testing of logic gates, counter testing and timer testing. How to upload a ladder diagram to a micro PLC via a computer using the K150 programmer and Microbrn software to upload the program to a micro PLC so that the input and output modules can work according to the ladder diagram programming that has been made. From the results of micro PLC testing can be used as a PLC learning media.